خطوط غالب کے ادوار (Al-Aasar, 2025)
This research article critiques Dr. Syed Moin ur Rahman's theory of dividing Mirza Ghalib's letter-writing into two distinct periods. Dr. Rahman suggests that Ghalib's writing style shifted from a spontaneous and simple one before November 1858 to a more cautious and deliberate one after he realized his letters might be published. This study challenges this view by providing evidence that Ghalib's style remained conversational and uninhibited even after the proposed transition date.The article argues that the variation in Ghalib's writing style was not the result of changing times, but rather a reflection of the individuals he was addressing. A highly conscious and intelligent figure, Ghalib adapted his tone and language according to the recipient's personality, his relationship with him, and their social standing.The study concludes that Ghalib's writing style is a fundamental part of his personality, and that attempting to divide his letter-writing into distinct periods based on style is not a sound approach.